2014
DOI: 10.15740/has/ijpp/7.2/330-333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bioagents and fungicide against earlyblight disease of tomato (Lycopersicon esculentum L.)

Abstract: An experiment was conducted to evaluate the effect of bio agents (Trichoderma harzianum and Pseudomonas fluorescens) and fungicides (mancozeb) against earlyblight of tomato caused by Alternaria solani (Ell. and Mart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The better performance of BCA against Phomopsis leaf blight and fruit rot might be due to increased soil suppressiveness and better plant growth. In controlling early blight of tomato caused by Alternaria solani, the findings of Zghair et al (2014) achieved from seed treatment and foliar spray of T. harzianum (24.33%) as against control (33.47%) were comparable with the performance of our consortia of BCA. In this case, T. harzianum might have affected spore germination and mycelium development of the pathogen that resulted into inhibition of disease producing activity and induced resistance in the plant (Zghair et al 2014).…”
Section: Effect Of Consortia Of Biocontrol Agents and Biofertilizer Against Diseases Of Brinjal In Field Conditionsupporting
confidence: 76%
See 1 more Smart Citation
“…The better performance of BCA against Phomopsis leaf blight and fruit rot might be due to increased soil suppressiveness and better plant growth. In controlling early blight of tomato caused by Alternaria solani, the findings of Zghair et al (2014) achieved from seed treatment and foliar spray of T. harzianum (24.33%) as against control (33.47%) were comparable with the performance of our consortia of BCA. In this case, T. harzianum might have affected spore germination and mycelium development of the pathogen that resulted into inhibition of disease producing activity and induced resistance in the plant (Zghair et al 2014).…”
Section: Effect Of Consortia Of Biocontrol Agents and Biofertilizer Against Diseases Of Brinjal In Field Conditionsupporting
confidence: 76%
“…In controlling early blight of tomato caused by Alternaria solani, the findings of Zghair et al (2014) achieved from seed treatment and foliar spray of T. harzianum (24.33%) as against control (33.47%) were comparable with the performance of our consortia of BCA. In this case, T. harzianum might have affected spore germination and mycelium development of the pathogen that resulted into inhibition of disease producing activity and induced resistance in the plant (Zghair et al 2014). Similar findings were also reported by several workers (Osowski 2003;Raziq and Ishtiaq 2010;Pawar et al 2013).…”
Section: Effect Of Consortia Of Biocontrol Agents and Biofertilizer Against Diseases Of Brinjal In Field Conditionsupporting
confidence: 76%
“…They also observed that in the combination of T. harzianum and P. fluorescens enhanced the plant growth. Zghair et al (2014) reported that seed treatment and foliar sprays of T. harzianum + P. fluorescens + Mancozeb gave lowest disease index. Thus, their combination not only suppressed the important pathogens of tomato but also promoted the growth of plant, which ultimately led to the increase in pesticide-free tomato production.…”
Section: Effect Of Bcas Amf and Fungicide Alone And In Combinationsmentioning
confidence: 99%
“…The application of T. harzianum in biological control showed a significant reduction in disease incidence, with some evidence supporting its ability to induce defense mechanisms in plants [ 6 ]. Zghair et al [ 7 ] reported that the biological preparation of T. harzianum can effectively reduce the disease intensity of tomato plants by increasing enzymatic antioxidants such as peroxidase, catalase, and polyphenol oxidase. The production of reactive oxygen species (ROS) and the antioxidants enzymes are the main indicator of early plant defense responses encountered by fungal pathogens [ 8 ].…”
Section: Introductionmentioning
confidence: 99%